2006
DOI: 10.1002/ana.20738
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid reduces levodopa‐induced dyskinesias in 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine monkeys

Abstract: These results suggest that DHA can reduce the severity or delay the development of LIDs in a nonhuman primate model of Parkinson's disease. DHA may represent a new approach to improve the quality of life of Parkinson's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…Then, combined oral administration of L-Dopa and DHA was performed on a daily basis for 1 month. Locomotor activity, as well as parkinsonian and dyskinetic scores of these animals have been previously reported (Samadi et al, 2006). All animals were sacrificed by an overdose of pentobarbital 4 hours after their last L-Dopa dose.…”
Section: Animals and Treatmentsmentioning
confidence: 87%
See 3 more Smart Citations
“…Then, combined oral administration of L-Dopa and DHA was performed on a daily basis for 1 month. Locomotor activity, as well as parkinsonian and dyskinetic scores of these animals have been previously reported (Samadi et al, 2006). All animals were sacrificed by an overdose of pentobarbital 4 hours after their last L-Dopa dose.…”
Section: Animals and Treatmentsmentioning
confidence: 87%
“…We previously reported the behavioral data of concomitant administration of DHA with L-Dopa (Samadi et al, 2006). This study showed that DHA significantly reduced LID scores in MPTP-treated monkeys without altering the anti-parkinsonian activity of L-Dopa (Samadi et al, 2006).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, as in patients with AD, in the brains of people with PD it is also observed a significant decrease in the levels of n-3 LCPUFA, especially DHA (Johnson et al, 1999). Research in primates allow to observe a significant reduction in the extent of levodopa-induced dyskinesia (a damage model for the PD) in animals supplemented with DHA, which suggests that these effects would be mediated by the activation of retinoid X receptors (RXR) (Samadi et al, 2006). In addition, data from these investigations show a drastic drop in neural DHA levels (Julien et al, 2006;Breckenridge et al, 1973).…”
Section: Dha and Parkinson´s Diseasementioning
confidence: 99%